Meme review a rhetorical analysis on local political internet memes and its roles on UP Diliman students' perception and behavior towards political participation - Fulay, Esteban M. Jr (College of Arts and Letters, University of the Philippines Diliman, 2019)
This study dealt with relevant ideas such as the current disposition of the youth in political realm, the role of internet in political discourse, the rhetorical development of entertainment memes to political memes, the continuous debate regarding online activism, the future activism, and most especially a possible glimpse of the fate of the Philippines in the hands of the youth. The study explored how UP Diliman students perceive the role of political memes on their perception and behavior towards political participation. It aimed to do that attending to these four objectives: 1) To describe the social media attitude and behavior of UP Diliman students;2) To examine selected local political internet meme's visual rhetoric components: symbolic aspects, human intervention and, audience; 3) To discuss how selected UP Diliman students evaluate the nature and function of the selected local political internet memes,and;4) To analyze how UP Diliman students perceive the roles of local political internet memes in their perception and behavior towards political participation. This study relied on visual rhetoric by Sonja K. Foss (2004) to provide the components that investigates the rhetoricity of the memes while also making use of Harol Laswell's (1948) model of communication to provide a communication process. The analyses were comprised of the researcher's content analysis and three focus group discussions. The participants of the FGDs were UP Diliman undergraduate students (A.Y. 2018-09207) that used Facebook everyday. The results showed that the students view memes mainly as form of entertainment. For them, creators make memes to attack a certain person or movement through meme's humor attribute and the memes should be relatable in order to be effective. In terms of the memes' roles it was limited to online being an avenue to share information, an avenue for research, and a form of encouragement for students to politically participate online.